1996
DOI: 10.1515/zna-1996-0808
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Behaviour of 1-(4-Isothiocyanatophenyl)-2-(4-hexyl- bicyclo[2,2,2]octane-1)ethane in Nematic and Isotropic Phases

Abstract: Static and dynamic investigations of the dielectric properties of the liquid crystal l-(4-isothiocyanatophenyl)-2-(4-hexyl-bicyclo[2,2,2]octane-l)ethane in the nematic and isotropic phases have been carried out in the frequency region from 1 kHz to 1 GHz. Two relaxation processes, described by the Debye functions, have been observed not only in the isotropic but also in the nematic phase, when the measurements of the electric permittivity vs. frequency have been made parallel to the orientation axis of liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…It has been shown that such a theoretical calculation of S agrees fairly well with experimental results obtained by various methods at ambient pressure as well as at higher pressures [9,10]. In this work we apply such calculations for the analysis of recently obtained high-pressure dielectric data.…”
Section: Introductionsupporting
confidence: 71%
“…It has been shown that such a theoretical calculation of S agrees fairly well with experimental results obtained by various methods at ambient pressure as well as at higher pressures [9,10]. In this work we apply such calculations for the analysis of recently obtained high-pressure dielectric data.…”
Section: Introductionsupporting
confidence: 71%
“…The nematic potential causes the long-range orientational order and hinders the rotation of the molecules around the short axis, so the corresponding relaxation time is significantly longer than that in the isotropic phase. This fact allows one to determine the height of the nematic potential barrier and thus the orientational order parameter from the dielectric data [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%